The Destruction of Architecture - Federico De Matteis (Footprint)
The Allied bombing campaigns over the German cities during World War II produced a vast landscape of destruction, which has been the object of reports, accounts and fictional narratives. Cities and buildings, a fundamental architectural heritage binding individuals and communities to their existential spaces, were annihilated in the most extensive act of deliberate destruction in human history. In this article, I look into the work of three authors – Heinrich Böll, Stig Dagerman and Hans Erich Nossack – to outline the effects of the bombings on the survivors, and on their relationship to both urban space and architectural heritage.